Optimal control theory with applications to resource and environmental economics - Michael Hoel (University of Oslo, Department of Economics, 2016)
This note gives a brief, non-rigorous sketch of basic optimal control theory, which is a useful tool in several simple economic problems,such as those in resource and environmental economics. While the mathematical analysis in the note is self-contained, there is not much explanation and intuition on the economic issues. The note should therefore be read together with articles or books that give more discussion of the economics of the problems considered.
Keywords: C61; Q2; Q3; Q5; 330; optimal control theory; exhaustible resources; renewable resources; climate change; water management